Childhood attachment and adult attachment in incarcerated adult male sex offenders - Smallbone, Stephen W. (Journal of interpersonal violence, 1998)
Forty-eight incarcerated sex offenders were compared with 16 property offenders and 16 nonoffenders on self-report measures of childhood maternal and paternal attachment and adult attachment. The combined sex-offender groups reported significantly less secure maternal, paternal, and adult attachment than did the nonoffenders and significantly less secure maternal attachment than did the property offenders. Intrafamilial child molesters were found to have had particularly problematic relationships with their mothers, reporting a combination of anxious and avoidant qualities in their maternal attachment experiences. By contrast, stranger rapists were found to have had particularly problematic relationships with their fathers and were significantly more likely to have regarded their fathers as having been characteristically unsympathetic, uncaring, abusive, and violent toward them. These results suggest that insecure childhood attachments may be related to offending behavior generally and that certain combinations of childhood attachment experiences may relate more specifically to different kinds of sexual offending